Health-Related Quality of Life in Patients With High-Grade Glioma: A Systematic Review. (1st October 2022) - Sanpher, Elen; Mitchell, Layla; Keshwara, Sumirat; Islim, Abdurrahman; Jenkinson, Michael; Millward, Christopher
Abstract: AIMS: Several studies have evaluated health-related quality of life (HRQoL) through patient-reported outcomes (PROs) in high-grade glioma (HGG) patients. No systematic review has summarised this increasingly important research area. METHOD: Seven electronic databases were systematically searched. Primary research articles evaluating HRQoL in HGG patients through PRO assessment were included. Global, physical, mental, and social health were summarised descriptively. Risk of bias (RoB) of included studies was assessed using The Joanna Briggs Institute Critical Appraisal tool or Newcastle Ottawa Scale. Quality of study reporting was assessed using a modified ISOQOL checklist. RESULTS: Twenty-six studies were included (4, 451 patients): cross-sectional (n=14), longitudinal (n=12). RoB and quality of reporting were satisfactory. Ten PRO measurement instruments were identified, of which EORTC-QLQ-C30 (n=15) was utilised most frequently. Fatigue significantly impacted both physical and global health. HRQoL improved after surgery but recurrence, fatigue, and difficulties with activities of daily living were associated with worsening HRQoL. HGG patients had higher anxiety and depression scores than the general population, negatively impacting overall HRQoL. Social health was superior for patients with good supportive networks, but a majority do not return to full-time employment post-diagnosis. Long-term survivors reported improvements in their physical, social and emotional functioning over time. CONCLUSION: With HGG life expectancy less than 12 months post-diagnosis, HRQoL is of paramount importance to patients. PRO assessment of HRQoL can be used to evaluate self-reported functioning and well-being in both routine practice and clinical trial settings and provide opportunities for timely intervention.